PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG ATAS BARANG YANG DIGUGAT OLEH PIHAK KTIGA, STUDI KASUS : PUTUSAN MA Nomor 2839 K/Pdt/2003 - MEMEY NATASHA (PREMISE LAW JURNAL, 2016)
People are usually interested in selling goods through auction because an auction can give some benefits and goodness, compared with the other systems in giving legal certainty. The implementation of auction in Batam is generally done by KPKNL which usually performs auction which is bound with fiduciary collateral or hypothecation. Regulation on auction guarantees legal certainty but does not always give legal protection to the winner of foreclosure sale as it can be seen in the case of auction done by KPKNL in Batam: the auction of other people’s goods. The problem of auction is general about the complaint from the third party so that the winner becomes a defendant. Therefore, bidders should be careful in buying other people’s goods in foreclosure sale and legal protection should be available for winners which are claimed by the third party. Bidders’ good faith in fulfilling their responsibility in the auction process is very vital in getting legal protection when they become the winners, and the implementation is realized by the issuance of auction letter as legal certainty for owning the goods. Auction letter is a kind of preventive legal protection for winners; therefore, when it is cancelled by court’s verdict which causes harm and when there is a claim for winners, they actually have the right to get repressive legal protection and responsibility from stakeholders, either from the goods sale or from KPKNL.   Keywords:       Legal Protection, Auction Winner, Goods complained by the Third Party